2021
DOI: 10.1002/jgc4.1393
|View full text |Cite
|
Sign up to set email alerts
|

CDH1 variants leading to gastric cancer risk management decision‐making experiences in emerging adults: ‘I am not ready yet’

Abstract: Pathogenic/likely pathogenic variants (PLPV) in CDH1 are associated with a significantly increased lifetime risk for diffuse gastric cancer, with an average age of onset of 47 years. CDH1 PLPV carriers are recommended to have prophylactic total gastrectomy (PTG) or routine endoscopy surveillance. Emerging adults (EAs) may have unique circumstances that affect their medical management decision‐making about PTG versus endoscopy. The study aim was to use qualitative interpretative phenomenological analysis method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
1
6
1
Order By: Relevance
“…For some, the decision to undergo PTG was simple; their lived and familial experience of gastric cancer and gastric cancer-related deaths caused a high degree of risk aversion, and PTG was the only option they considered. This finding is incongruent with recently published findings in a similarly aged cohort in the United States of America, whereby the majority of their participants did not feel ready to pursue PTG even in the setting of lived or familial experience (Liu et al, 2021).…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…For some, the decision to undergo PTG was simple; their lived and familial experience of gastric cancer and gastric cancer-related deaths caused a high degree of risk aversion, and PTG was the only option they considered. This finding is incongruent with recently published findings in a similarly aged cohort in the United States of America, whereby the majority of their participants did not feel ready to pursue PTG even in the setting of lived or familial experience (Liu et al, 2021).…”
Section: Discussioncontrasting
confidence: 89%
“…These participants understood the nuances and challenges of the screening procedure; however, they also described a sense of trust in the healthcare providers. The authors speculate whether the increasing confidence in endoscopic surveillance in recent years has permitted health professionals to safely offer this as a risk management option, particularly as this increase in trust in surveillance is reflected in two additional studies published within the last year (Liu et al, 2021;McGarragle et al, 2020). The downstream effect of this alters the implications for and discussions with the current patients of clinical genetics services when considering the risk management options for CDH1 PV carriers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As reported by Liu and colleagues, 8 emerging adult CDH1 PLPV carriers expressed that dietary restrictions, nutrition implications, and lifestyle changes after PTG weigh heavily in their medical management decision making. McGarragle and colleagues 9 also reported that individuals at risk of HDGC reported lifestyle changes after total gastrectomy as a barrier to proceeding with PTG and that younger individuals reported fear of losing their good health and fitness if they were to undergo PTG.…”
Section: Emerging Adults Face Postetotal Gastrectomy Diet and Lifesty...mentioning
confidence: 90%